Status of occupational hazards and their prevention among dental professionals in Chandigarh, India: A comprehensive questionnaire survey - Abhishek Mehta; Mohit Gupta; Nancy Upadhyaya (Wolters Kluwer Medknow Publications, 2013)
Background: To assess the status of occupational hazards and their prevention among the practicing dentists in Chandigarh city, India. Materials and Methods: A closed-ended questionnaire was prepared to record demographic status, types of occupational hazards encountered, and status of measures used for their prevention. A total 113 out of 130 dentists completed the questionnaire and the response rate was 86.9%. Frequency tables were prepared and coefficient of correlation was computed to check correlation between different variables. Statistical significance was set at P < 0.05. Results: The most common occupational hazard reported was injury from "sharps" (77%), out of which needle prick injury was the most frequent. Of the other occupational problems job related stress (43.3%), musculoskeletal problems (39.8%), and allergies (23.8%) from things used in dental clinics were most common. A reasonably high percentage of dentists were immunized against hepatitis-B virus (88.4%) and were following proper infection control measures and hospital waste disposal methods. Very few dentists were following the correct method of disposal of excess amalgam (11%) and measurement of radiation exposure (27.5%) within their clinic. Most of them (90.2%) were satisfied with their current working hours and job. Conclusion: Prevalence of occupational hazards among the studied group was high and certain preventive measures were not being followed properly. Therefore, there is a need to improve the knowledge of dentists regarding these hazards and their prevention.